Evolusi Manajemen Operasional di Era Digital: Tantangan dan Peluang - Berkat Jaya Zalukhu; Omi Nilai Murni Waruwu; Siti Nur Aisya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The advancement of digital technology has revolutionized the way companies manage their business operations. Operational management is no longer limited to process efficiency, but has evolved into an adaptive, data-driven system supported by advanced technologies such as artificial intelligence, the Internet of Things (IoT), big data analytics, and cloud computing. This article aims to explore the evolution of operational management in the digital era by identifying major challenges such as the digital skill gap, technological infrastructure limitations, and organizational resistance to change, while also examining strategic opportunities such as automation, enhanced efficiency, and data-based decision making. Using a qualitative approach through literature review, this study provides both theoretical and empirical perspectives on the importance of operational innovation in building competitive advantage amid ongoing digital disruption.